Paving a path to essentialize an “imagined” community: inquiring the contemporary music culture in the digital age through virtual ethnography - Chow, Ow Wei (Peter Lang Group AG, 2024)
This paper regards internet users who “convene” in moderated groups according to a common interest, social attachment, or other multiple intersected connections as an “imagined” community that surfaces on a social networking platform. The validity of the community, especially when being of an ethnographer’s interest, is argued through a documentation of responses captured and operated as ethnographic data. This is a preliminary study of music culture in the digital age through online survey as virtual ethnography to explore a glimpse of the reality via reactions of an “imagined” community. Through a systematic and critical presentation of the ethnographic data, music culture in the contemporary time is interpreted as a trajectory which significantly essentializes an “imagined community” as genuine as a physical field site in the light of cultural musicology.